A water-stable zinc metal-organic framework as fluorescent probe for simultaneously sensing of glutathione and cysteine. (October 2022) - Yue, Dan; Zhu, Jiayan; Chen, Dong; Li, Weidong; Qin, Bowen; Zhang, Bing; Liu, Deri; Yang, Xiaotong; Zhang, Yilei; Wang, Zhenling
Abstract: Glutathione (GSH) and cysteine (Cys) have similar structures but play different roles in biological systems, so it is important to realize simultaneously and effectively detect them in biomedical field such as disease diagnose, etc. Herein, a water-stability and spindle shape zinc metal-organic framework (Zn-DTBA) with the ligand (2′-dithiodibenzoic acid, H2 DTBA) has been successfully obtained for simultaneously detecting GSH and Cys. Cys can react with the disulfide bond in H2 DTBA, thereby destroying the crystal structure of Zn-DTBA and quenching the fluorescence. GSH can act on the junction between the ligand and the metal node during the detection process, causing the collapse of Zn-DTBA structure and releasing Zn 2+ ion and ligand. Therefore, Zn-DTBA has different fluorescence response for GSH and Cys, and the limit of detection (LOD) for the sensing of GSH and Cys was estimated to be 0.28 and 0.76 μM respectively. In further, Zn-DTBA can be successfully applied to detect Cys and GSH in serum as well, which is conducive to expand the application range of Zn-DTBA in practical detection. This investigation indicates that Zn-DTBA can be used as a potential fluorescent probe for the future biological studies of biothiols sensing. Highlights: Zn-DTBA exhibits high water stability and pH stability. The LOD of Zn-DTBA for the sensing of GSH and Cys is estimated to be 0.28 and 0.76μM respectively. Zn-DTBA can be successfully applied to simultaneously detect Cys and GSH in serum.